Radical scavenging activity and phytochemical investigation of antioxidative compounds from stem and leaves of leea indica species / Aiza Harun ...[et al.] - Harun, Aiza; Daud, Shaari; Harith, Siti Suhaila; Ab Rahim, Nor Erlena Asmira; Abd Jalil, Mohd Azfar; Muhammad Rosdi, Nurul 'Atiqah; Baharom, Fatin Azieyati; Mohd Azam, Naila Nabihah; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian (Universiti Teknologi MARA Cawangan Pahang, 2018)
In this paper, the potency of stem and leave extracts of Leea indica locally known as Memali from Tasik Chini, Pahang as a potent antioxidant agent had been studied. The antioxidant properties of three types of extracts was quantitatively assessed by 2,2 diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. The isolation of antioxidative compounds was conducted through preparative thin layer chromatography with the use of certain binary solvents. The structure determination was carried out using Gas Chromatography Mass Spectrometer (GCMS). The methanol extracts from both stem and leaf exhibited highest antioxidant activity with lowest IC50 of 1.14 ug/ml and 81 ug/ml respectively compared to other extracts. The stem showed stronger antioxidant activity compared to leaves part. Based on GCMS analysis, the antioxidative compounds isolated from leaves part were proposed as 6-Hyroxy-4,4, 7a-trimethyl-5,6,7,7a-tetrahydrobenzofuran-2(4H)-one (1), 3,8,8-Trimethoxy-3- piperidyl-2,2-binaphthalene-1,1,4,4-tetrone (2), Methyl stearate (3), 9,12-Octadecadienoic acid (4), Palmitic acid (5) and9- Oxononanoic acid(6). The antioxidative compounds isolated from stem part were determined as oleic acid (7), 1-(hydroxymethyl)-1,2- ethanediyl ester (8) and 9-octadecene (9). This finding can be used as scientific baseline information for the future treatment of diseases caused by harmful free radicals.